Politik Kepentingan : (Analisis Historis Kasus Ab? Muslim al-Khurasan? di Masa Daulah Umaiyah dan Abbasiyah) - Nasution, Syamruddin (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2013)
At the end of 2013 and beginning of 2014 we were presented the spectacle of government for maintaining ‘political interests’, that was the arrest of a number of politicians, and among them is the suspects in the Hambalang, Anas Urbaningrum, and Antasari Azhari before, chairman of the Corruption Eradication Commission (KPK). Two of these cases may be as a representative example of the case that the same modus, are killing characters of politicion for political interests. It turns out that these cases also occurred in early Muslim history, even kill each other. One example was the case of Ab? Muslim alKhurasan?, one of the major meritorious and has a big hand in toppling Umaiyah Daulah and established the Abbasid Daula. Initially Abu Muslim was appointed by Ab? Abb?s a?-?affah, the first Caliph of the Daulah Abbasid, to become governor of Khurasan, but was then killed by Abu Ja‘far al-Mansur, 2nd Caliph of Abbasids. This paper attempts to describe the case of Ab? Muslim alKhurasan?, a politician who was killed by his own at the beginning of the Daulah Abbasid. This study addresses three problems. First, how the events that befall Ab? Muslim al-Khurasan?. Secondly, why Ab? Muslim al-Khurasan? was killed. Third, what is the relevance of studying and knowing murder of Ab? Muslim al-Khurasan? to political life in Indonesia by contextualization.